Dropless penetrating keratoplasty using a subconjunctival dexamethasone implant: safety pilot study. Issue 2 (23rd August 2021) - Trone, Marie Caroline; Poinard, Sylvain; Crouzet, Emmanuel; Garcin, Thibaud; Mentek, Marielle; Forest, Fabien; Matray, Marie; Thuret, Gilles; Gain, Philippe
Abstract : Background/aim: Rejection is the main cause of graft failure after penetrating keratoplasty (PK). Its prevention by repeated instillation of steroid eye-drops has not evolved in decades. Poor adherence and discontinuous nature of eye-drop treatment may explain some PK failures. In a rabbit model, we previously demonstrated that a subconjunctival dexamethasone implant was well tolerated and prevented rejection efficiently in the first 5–6 weeks. This clinical trial investigates its tolerance and safety after PK. Methods: Single-centre, phase II non-randomised tolerance and safety pilot study (NCT02834260 ). Designed to analyse the risk of elevated intraocular pressure (IOP), discomfort and resorption time. Fourteen patients with a low rejection risk indication of PK were enrolled between January 2017 and August 2018. The implant was injected in the 12 o'clock position, 5 mm from the limbus, at the end of PK. A steroid eye-drop treatment was planned when implant resorption was complete. Patients were monitored regularly for 12 months: IOP (main outcome measure at 1 month), discomfort and redness scores, implant status, rejection episode and central corneal thickness by optical coherence tomography. An independent data safety monitoring committee verified safety aspects. Results: No increase in IOP or other adverse event related to the implant was observed. Average resorption time was 6 weeks. The switch to steroid eye-drops was uneventful. One patient, included despite preoperative corneal neovascularisation (unintended protocol deviation) experienced a rejection. Conclusions: This is the first proof of concept that dropless immunosuppression is possible after low rejection risk PK. Trial registration number: NCT02834260 .